A Bioglass-Based Antibiotic (Vancomycin) Releasing Bone Void Filling Putty to Treat Osteomyelitis and Aid Bone Healing - Hasan, Raquib (Int J Mol Sci, 2021)
While the infection rate after primary total joint replacements (TJR) sits at 1–2%, for trauma-related surgery, it can be as high as 3.6 to 21.2% based on the type of trauma; the risk of reinfection after revision surgery is even higher. Current treatments with antibiotic-releasing PMMA-based bone cement/ beads and/or systemic antibiotic after surgical debridement do not provide effective treatment due to fluctuating antibiotic levels at the site of infection, leading to insufficient local antibiotic concentration. In addition, non-biodegradable PMMA does not support bone regrowth in the debrided void spaces and often must be removed in an additional surgery. Here, we report a bioactive glass or bioglass (BG) substrate-based biodegradable, easy to fabricate “press fitting” antibiotic-releasing bone void filling (ABVF-BG) putty to provide effective local antibiotic release at the site of infection along with support for bone regeneration. The ABVF-BG putty formulation had homogenously distributed BG particles, a porous structure, and showed putty-like ease of handling. Furthermore, the ABVF-BG putty demonstrated in vitro antibacterial activity for up to 6 weeks. Finally, the ABVF-BG putty was biodegradable in vivo and showed 100% bacterial eradication (as shown by bacterial cell counts) in the treatment group, which received ABVF-BG putty, compared to the infection control group, where all the rats had a high bacterial load (4.63 × 10(6) ± 7.9 × 10(5) CFU/gram bone) and sustained osteomyelitis. The ABVF-BG putty also supported bone growth in the void space as indicated by a combination of histology, µCT, and X-ray imaging. The potential for simultaneous infection treatment and bone healing using the developed BG-based ABVF-BG putty is promising as an alternative treatment option for osteomyelitis.